Prognostic Impact of the International Society on Thrombosis and Hemostasis Disseminated Intravascular Coagulation Score in Sepsis: A Systematic Review - Frank, Christian Sandberg; Larsen, Julie Brogaard (Seminars in Thrombosis and Hemostasis, 2023)
The International Society on Thrombosis and Haemostasis (ISTH) diagnostic criteria for disseminated intravascular coagulation (DIC) are widely used for DIC diagnosis. However, the prognostic value of the score may vary between different patient populations and settings. This systematic review investigated the association between the ISTH DIC score and mortality in sepsis patients. A literature search was conducted in PubMed and Embase. Inclusion criteria were studies including adult and pediatric patients hospitalized with sepsis, using any sepsis definition, and investigating the association between mortality and the ISTH DIC score. The review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. In total, 42 studies were included. A positive association between the ISTH DIC score and mortality was consistently reported, with odds ratios of death in DIC versus non-DIC patients ranging from 1.125 (95% confidence interval [CI]: 0.838–1.511) to 21.008 (95% CI: 1.408–313.405) in adults and from 1.378 (95% CI: 1.004–1.893) to 2.99 (95% CI: 0.54–16.6) in pediatric populations. However, the DIC score only had a low-moderate positive predictive value for mortality, as area under receiver-operator characteristics ranged from 0.602 (95% CI: 0.575–0.630) to 0.815 (95% CI: 0.676–0.954) in adults. Of note, only few studies adjusted for potential confounders such as age, gender, and comorbidity. The ISTH DIC score is consistently associated with sepsis-related mortality but is not a strong positive predictor for mortality. Nevertheless, the score may still have a prognostic value and its use in sepsis is encouraged.
Keywords: disseminated intravascular coagulation; sepsis; prognosis; mortality